The non-adult citizen masculinity: the ‘genderization’ of male children in Classical Athens - Kibuuka, Brian (Romanitas - Revista de Estudos Grecolatinos, 2023)
This article addresses the intersection between generation, gender and social status in the genderization of boy citizens in Classical Athens from the analysis of rites related to birth, insertion of boys in a collective and polyad context; and male gender in the school context, in children's play and games and in ephebia. The analysis carried out in this article of the social practices that corroborate the identification and adequacy of children identified sexually as male culminates in the recognition of a process of introducing boys into homosocial practices, in addition to inserting them in an oikiad and polyad context according to the required normative practices of male citizens in Athens. Such genderization makes the program for acquiring superior masculinity the context in which “good masculinity” is engendered, constituted in itself as a stereotype and parameter for gendering practices.
Keywords: Genderization; Childhood; Classical Athens